The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1042/bsr20201854
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic irradiation and SonoVue microbubbles-mediated RNA interference targeting PRR11 inhibits breast cancer cells proliferation and metastasis, but promotes apoptosis

Abstract: This study compared the effects of ultrasonic irradiation and SonoVue microbubbles (US) or Lipofectamine 3000 on the transfection of small interfering RNA for PRR11 (siPRR11) and PRR11 overexpression plasmid into breast cancer cells. SiPRR11 and PRR11 overexpression plasmid were transfected into breast cancer MCF7 cells mediated by US and Lipofectamine 3000. PRR11 expressions in breast cancer and normal tissues were determined using Gene Expression Profiling Interactive Analysis (GEPIA). The viability, prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Other studies highlighted that UTMD of miR-133a could inhibit the tumor growth and improve the survival rate in breast cancer mice [ 38 ], and UTMD of Cav1.3 siRNA exerted antitumor effects on breast cancer [ 39 ]. In addition to the aforementioned literature’s illustration of the feasibility of UTMD as a gene transfection modality to treat breast cancer, another study by Hui Luo et al evidenced that silenced PRR11 mediated by US exhibited a higher efficiency than that mediated by lipofectamine 3000 [ 40 ]. Besides, Xiaojiang Tang et al proved that the inhibitory effect of UTMD-mediated SOCS3 on the biological behavior of breast cancer cells was better than that of liposome-mediated SOCS3 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies highlighted that UTMD of miR-133a could inhibit the tumor growth and improve the survival rate in breast cancer mice [ 38 ], and UTMD of Cav1.3 siRNA exerted antitumor effects on breast cancer [ 39 ]. In addition to the aforementioned literature’s illustration of the feasibility of UTMD as a gene transfection modality to treat breast cancer, another study by Hui Luo et al evidenced that silenced PRR11 mediated by US exhibited a higher efficiency than that mediated by lipofectamine 3000 [ 40 ]. Besides, Xiaojiang Tang et al proved that the inhibitory effect of UTMD-mediated SOCS3 on the biological behavior of breast cancer cells was better than that of liposome-mediated SOCS3 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PRR11 blocked p85 homodimerization and sensitized to ligand-induced PI3K activation, suggesting that PRR11 amplification confers resistance to estrogen deprivation through hyperactivation of the PI3K pathway [ 1 ]. Notably, ultrasonic irradiation and SonoVue microbubbles-mediated RNA interference targeting PRR11 could exert anti-cancer effects via PRR11 [ 41 ]. However, the oncogenic role of PRR11 in vivo is still blurred, demanding additional exploration.…”
Section: Oncogenic Role Of Prr11 In Various Malignanciesmentioning
confidence: 99%
“…Preliminary experiments found that SonoVue microbubbles-mediated RNA interference targeting PRR11 could exert anti-cancer effects, forecasting the potential application of PRR11 for targeted therapy [ 9 , 41 ]. In the meanwhile, circRNA_cZNF292 was involved in angiogenesis of glioma through PRR11 [ 77 ].…”
Section: Prr11 Involved Targeted Therapies In Various Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…PRR11 is highly expressed in many human cancers and has been regarded as a potential biomarker for poor prognosis 9–14 . Moreover, numerous studies have shown that PRR11 participates in the tumorigenesis and development of many cancers, such as lung cancer, hepatocellular carcinoma, osteosarcoma, clear cell renal cell carcinoma, breast cancer, tongue squamous cell carcinoma (TSCC), esophageal squamous cell carcinoma, and pancreatic cancer 15–22 …”
Section: Introductionmentioning
confidence: 99%